Rab21 recruits EEA1 and competes with Rab5 for Rabex-5 activation - Yanguas, Francisco; Progida, Cinzia (Frontiers in Cell and Developmental Biology, 2025)
Rab5 is a key regulator of early endosomal traffic and fusion. It shares its localization and guanine nucleotide exchange factor Rabex-5 with the less characterized member of the Rab5 subfamily Rab21. Here, we found that, similarly to Rab5, Rab21 also interacts with the tethering protein EEA1. Overexpression of Rab21 rescues the defects in EEA1 localization and endosomal size caused by the depletion of PI3P or the inhibition of Rab5 function, both needed for the recruitment of EEA1 to early endosomes. Interestingly, modulation of the binding properties of Rab5 or Rab21 dominant negative mutant with Rabex-5 support a model in which Rab5 and Rab21 compete for the activation by Rabex-5 and suggest that Rab21 might have higher affinity for this GEF than Rab5 in vivo. Altogether, our results reveal that Rab21 regulates early endosomal size by recruiting EEA1 to the endosomes via a pathway parallel to Rab5 and highlight Rabex-5’s critical role in Rab21 and Rab5 cross-regulation.